Study of thiamine and its metabolites on RNA synthesis with exogenous nucleotides - Yakimenko, V. E.; Petrov, S. A.; Nikolayenko, K. V. (Journal of Education, Health and Sport, 2017)
The influence of thiamine and its metabolites for introducing nucleotides in the incubation medium content of RNA in the blood of white rats. It is shown that this thiamine and its main katabolit - tiohrom, can increase levels of RNA in the blood as without and with the presence of exogenous nucleotides.. At the same time, it was noted that the introduction into the environment of nucleotides showed a more positive effect. It was found that other metabolites of thiamine do not significantly affect the biosynthesis of RNA. It was also noted that in the liver of white rats after the introduction of vitamin B1 and its metabolites, changes occur from the second hour of the study, and in four hours only thiamine and thiochrome have a positive effect. In the rat brain, the positive effect was recorded only after administration of thiochrome. According to the study, it was found that thiochrome had the greatest effect on the content of RNA, a less favorable effect was observed in the introduction of thiamine. At that time, other metabolites of thiamine did not show a positive effect, which makes it possible to consider them ineffective when exposed to the content of RNA.